Effectiveness of Fall Prevention Education on Nurses' Compliance and Patient Safety Attitude: Experimental Study in Elderly - Liany Kimberly; Azizah Khoiriyati (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Falls pose a significant challenge in elderly hospital care, often resulting in severe injuries and increased morbidity risk. Two critical factors in reducing fall incidence are nurses' adherence to fall prevention protocols and their attitudes toward patient safety. The Fall Tailoring Intervention for Patient Safety (TIPS) toolkit is an innovative tool designed to enhance nurses' awareness and implementation of fall prevention strategies. However, its adoption in Indonesian hospitals remains limited, necessitating further research on its effectiveness. This study aims to evaluate the impact of the Fall TIPS toolkit on fall prevention by assessing its influence on nurse compliance and patient safety attitudes. Using a quasi-experimental pre-posttest design with a control group, this study involved 52 nurses from the adult inpatient unit of a private hospital in Manado, Indonesia. Participants were divided into an intervention group and a control group. Data on compliance and patient safety attitudes were collected through questionnaires. The Wilcoxon test showed no significant difference in nurse compliance before and after the intervention (p > 0.05), but a significant improvement was observed in patient safety attitudes (p < 0.05). Additionally, Mann-Whitney test results indicated a significant difference between the intervention and control groups in both compliance and patient safety attitudes. The findings suggest that the Fall TIPS toolkit is an effective strategy for enhancing nurses' compliance and patient safety attitudes in hospital settings. To ensure sustained adoption and effectiveness in fall prevention, hospitals are encouraged to integrate the toolkit into standard nursing protocols and provide continuous training.Keywords: Compliance, Fall Prevention Education, Safety attitude